Space habitats for bioengineering and surgical repair: addressing the requirement for reconstructive and research tissues during deep-space missions - Alexandra Iordachescu; Neil Eisenstein; Gareth Appleby-Thomas (npj Microgravity, 2023)
Abstract Numerous technical scenarios have been developed to facilitate a human return to the Moon, and as a testbed for a subsequent mission to Mars. Crews appointed with constructing and establishing planetary bases will require a superior level of physical ability to cope with the operational demands. However, the challenging environments of nearby planets (e.g. geological, atmospheric, gravitational conditions) as well as the lengthy journeys through microgravity, will lead to progressive tissue degradation and an increased susceptibility to injury. The isolation, distance and inability to evacuate in an emergency will require autonomous medical support, as well as a range of facilities and specialised equipment to repair tissue damage on-site. Here, we discuss the design requirements of such a facility, in the form of a habitat that would concomitantly allow tissue substitute production, maintenance and surgical implantation, with an emphasis on connective tissues. The requirements for the individual modules and their operation are identified. Several concepts are assessed, including the presence of adjacent wet lab and medical modules supporting the gradual implementation of regenerative biomaterials and acellular tissue substitutes, leading to eventual tissue grafts and, in subsequent decades, potential tissues/organ-like structures. The latter, currently in early phases of development, are assessed particularly for researching the effects of extreme conditions on representative analogues for astronaut health support. Technical solutions are discussed for bioengineering in an isolated planetary environment with hypogravity, from fluid-gel bath suspended manufacture to cryostorage, cell sourcing and on-site resource utilisation for laboratory infrastructure. Surgical considerations are also discussed.